Grammatical Mistakes Analysis of the Students in the Class of Poetry Analysis at Faculty of Language and Literature in UNSIQ - Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2019)
This article presents the research result of teaching-learning in the lecture of Poetry Analysis towards the students of English Literature at Faculty of Language and Literature in Universitas Sains Al-Qur’an (UNSIQ). This article aims at analyzing grammatical mistakes in the Poetry Analysis class by taking the students’ final paper as the samples of main data. This study uses qualitative methodology. The collected data steps are identifying, classifying and selecting the main data which contain of grammatical mistakes. The analyzing data techniques are exposing and explaining the selected data. The theories applied in this study are related to some sources about correct and incorrect structures and arrangement of sentences in English. The results of this study show that some of the students made mistakes in arranging sentences especially in English parts of speech such as pronoun, noun and verb.